Impact of Transformational Leadership and Organizational Culture on The Performance of PT Indosaluyu Primajaya: Job Satisfaction as A Mediation Variable - Mafud Liansah; Irfan Noviandy Aulia (Dinasti International Journal of Management Science, 2022)
The purpose of this study is to determine whether satisfaction acts as a mediator between transformational leadership and organizational culture on the performance of PT Indosluyu Primajaya employees. The SEM-PLS Equation Model was used for data analysis with a sample of 99 employees. Based on the findings of this study, transformational leadership, and organizational culture have a positive and significant impact on performance through satisfaction. In addition, performance has a positive and significant impact because it is influenced by transformational leadership and job satisfaction. While job satisfaction is a perfect mediator of this effect, organizational culture has no direct or significant impact on employee performance. Organizational culture does not directly affect employee performance.